Meningkatkan Hasil Belajar Siswa Dalam Materi Pecahan Pada Mata Pelajaran Matematika Dengan Menggunakan Model Pembelajaran Problem Based Learning (PBL) - Iwan Setiawan; Rifki Arif Nugraha; Yeni Sulaeman; Ade Farid Hasyim (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
The research method used was the Class Action Research Method (CAR), which consisted of two cycles where each cycle was held in two meetings. The subjects in the research were 25 class V students at SDN Cipinang 3, Angsana District, Pandeglang Regency. Data collection instruments use observation sheets and tests. The data analysis technique used is qualitative descriptive analysis and quantitative descriptive analysis. The results of the research showed that there was an increase in student learning outcomes in mathematics subjects regarding fractions. In pre-cycle activities, 5 students completed their studies or around 20%. After carrying out the first cycle activities, the number of students who completed their studies became 13 students or around 52%. Meanwhile, in cycle II it was discovered that there was an increase in the number of students who completed their studies to 23 people or around 92%. The results of observations in cycle 1 meetings 1 and 2 which initially the percentage of success only reached 44.4% and 66.6% experienced a significant increase in cycle II meetings 1 and 2 namely 72% and 91.6%. The background to the increase in student learning outcomes in mathematics subject matter of fractions is the use of an effective and fun learning model so that it can motivate students' interest in learning to be better. The learning model used is the Problem Based Learning (PBL) learning model